Characteristics of Giardiasis and Enterobiаsis in children of Astrakhan region - R. S. Arakelyan; E. I. Okunskayu; N. A. Sergeeva; O. V. Konnova; Kh. M. Galimzyanov; G. L. Shendo; V. Sh. Sangadzhieva; P. K. Magomedova; A. N. Zagina (LLC "Diagnostics and Vaccines", 2019)
Purpose: assessment of the clinical and epidemiological situation of current invasions in children of the Astrakhan region. 315 outpatient cards of children were analyzed in 2016.The diagnosis of Giardiasis was made to 151 children, the diagnosis of Enterobiasis - 164. The age of all observed children ranged from 9 months to 17 years. The largest part was made up of children aged 3 to 14 years of age - 80.3%, among them enterobiasis was identified - in 46.7%, giardiasis - in 33.6% of cases. Most of the children  - 90.5% were from organized groups (they attended preschool institutions or school). The reasons for the examination of all children were varied. Some children - 63.5% went to the doctor with complaints  or clinical symptoms. Another part of the children - 33% of the diagnosis was made as a result of preventive examinations.In most cases - 78.7% various bad habits were identified. Thus, geophagy (the habit of eating the earth) was noted in 33.3% of children, and onigophagy (the habit of biting the nails) in 24.8%. In 21.3% of cases, bad habits were absent. Contact with pets was established in 22.9% of children. According to the ultrasound, most children with giardiasis (83.8%) had pathology (reactive changes of the pancreas, liver, gallbladder dyskinesia, etc.)In case of giardiasis niferator, albendazole was administered. In case of enterobiasis albendazole, pyrantel, and mebendazole were administered in age dosages. After antiparasitic treatment, in 91.4% of cases, the clinical symptoms of the disease completely disappeared, with giardiasis - in 85.4%, with enterobiasis - in 97% of cases.In 1.3% of children with giardiasis, after several courses of antiparasitic drugs, Giardia was found in feces in the absence of complaints and clinical symptoms, indicating a possible Giardia carrier parasite in children.